IDENTIFIKASI JAMUR PENYEBAB TINEA UNGUIUM PADA KUKU KAKI PETANI DI DUSUN BAROS TIRTOHARGO KRETEK BANTUL - Nadifah, Fitri; Muhajir, Nurlaili Farida; Sanusi , Kristi Elisabeth; Murtiningrum, Sri; Nuryati, Arum (JURNAL BIOSENSE, 2025)
Tinea unguium is a type of superficial mycosis that attacks the nail plate as a result of dermatophyte infection. This study aimed to identify the fungal genera responsible for tinea unguium in the toenails of farmers in Baros Hamlet, Tirtohargo Village, Kretek District, Bantul Regency. Thirteen nail samples were examined microscopically with 20 % KOH and Lactophenol Cotton Blue preparations, and cultured on Sabouraud Dextrose Agar (SDA). Three fungal genera were identified: Aspergillus (9 isolates), Penicillium (3 isolates) and Trichophyton (1 isolate). Hence, the dermatophyte causing tinea unguium in these farmers’ feet was Trichophyton sp. Microscopic observations revealed conidiophores, vesicles, phialides, and conidia consistent with the morphological characteristics of each genus. These results underscore the need for education on preventative measures, such as wearing appropriate footwear, maintaining foot hygiene, and increasing farmers’ awareness of the risk of fungal infection.